5th International Meeting for Researchers in Materials and Plasma Technology (5th IMRMPT). (November 2019) - Unknown
Abstract : E D V-Niño 1 1 Materials Science and Technology Research Group, Foundation of Researchers in Science and Technology of Materials, Colombia E-mail: deydannv@gmail.com, foristom@gmail.com These proceedings present the written contributions of the participants of the 5th International Meeting for Researchers in Materials and Plasma Technology (5th IMRMPT) which was held from 28 to May 31, 2019, at the San José de Cúcuta city, Colombia, organized by Foundation Of Researchers In Science and Technology Of Materials (FORISTOM). This was the fourth version of biennial meetings that began in 2011. The proceedings consist of 148 contributions that were presented as plenary talks at the conference. The abstracts of all participants contributions were published in the Abstract Book with ISSN 2422-3824. The website of the conference is available at http://foristom.org/5imrmpt/index.html. The fifth-day scientific program of the 5th IMRMPT consisted of 17 Magisterial Conferences, 111 Oral Presentations, 131 Poster Presentations, 3 Courses and 1 Discussion Panel with the participation of undergraduate and graduate students, professors, researchers and entrepreneurs from Colombia, Russia, Spain, Unite Kingdom, Mexico, Argentina, Uruguay, Brazil, Ecuador, Venezuela, among others. Moreover, the objective of IMRMPT was to bring together national and international researchers in order to establish a network of scientific cooperation with a global impact in the area of the science and the technology of materials; to promote the exchange of creative ideas and the effective transfer of scientific knowledge, from fundamental research to innovation applied to industrial solutions and to advance in the development of new research allowing to increase the lifetime of the materials used in the industry by means of efficient transference of the knowledge between sectors academia and industry. List of Organizing Committee / Comité Organizador Local, National Scientific Committee / Comité Académico Nacional, International Scientific Committee / Comité Académico Internacional, Invited Speakers / Conferencistas Invitados, Sponsor, Partners are available in this pdf.